THE ANALYSIS OF FOREIGN-VESSEL SINKING AS AN EFFORT BY THE GOVERNMENT OF INDONESIA TO COMBAT IUU FISHING PURSUANT TO INTERNATIONAL LAW - Kristiyanto, Kristiyanto (Brawijaya Law Journal, 2015)
As an archipelagic state, Indonesia possesses some of the most abundant fishery resources in the world. Geographically, Indonesia's strategic location makes it a challenge, and it is a shared responsibility for all citizens to preserve and conserve these resources. The strategic location and rich biological as well as non-biological marine resources automatically attract foreign vessels to carry out IUU fishing activities, particularly in the area of ZEEI (Indonesian Exclusive Economic Zone). The Government of Indonesia has taken various preventive measures to combat IUU fishing practices through bilateral cooperations and various laws. In addition, the Government has also taken some repressive efforts by burning and sinking foreign vessels. In this study, the researcher will analyze the governmental action pursuant to international law and examine the extent to which the sinking of the ship is effective from the perspective of international law. This study will be conducted using normative and juridical approach by reviewing and analyzing various national and international legal instruments related to IUU fishing. We hope that this study will be able to deliver theoretical and practical benefits for students and other researchers who are interested in the issue of IUU fishing practices.